Preparation method and application of double-gradient self-supporting hydrogen evolution electrode
By constructing longitudinal geometric gradients and lateral infiltration gradients on the surface of the electrocatalytic hydrogen evolution electrode, the problems of high overpotential and difficult increase in current density caused by bubble coverage during electrocatalytic hydrogen evolution are solved, and the electrode is efficient and stable and low-cost hydrogen gas are achieved. Production.
Patent Information
- Application Number
- CN202411451360.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During the electrocatalytic hydrogen evolution process, bubble coverage leads to high overpotential of the electrode and difficulty in increasing the current density. The prior art is difficult to effectively reduce the load of the catalyst precious metals and the cost of the electrode.
The preparation method of double-gradient self-supported hydrogen evolution electrode is adopted to reduce gas aggregation and bubbles by forming longitudinal geometric gradients and transverse infiltration gradients on the surface of the conductive carbon cloth. Coverage to promote in-situ separation of hydrogen.
The overpotential of the electrode under high current density is reduced, the electrode stability and hydrogen generation efficiency are improved, the loading of precious metal catalysts is reduced, and the electrode cost is reduced.
Smart Images

Figure CN119243213A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrocatalytic hydrogen evolution, and in particular to a preparation method and application of a dual-gradient self-supporting hydrogen evolution electrode. Background Art
[0002] Hydrogen has been regarded as an ideal energy carrier due to its advantages such as zero emission and high energy density. As for the source of hydrogen, electrocatalytic hydrogen evolution is a key technology that can be coupled with renewable energy such as photovoltaic and wind power. However, the high cost of its precious metal catalysts and the rapid decline in electrolysis performance under actual high current density have hindered the further industrial application of electrocatalytic hydrogen evolution technology.
[0003] For electrocatalytic hydrogen evolution, most current research focuses on reducing the manufacturing and use costs of electrolyzers by developing new catalysts and electrode materials. However, in actual operation, the effects of electrolysis products and bubbles on the performance of electrolyzers are often ignored. In the process of electrocatalytic hydrogen evolution, bubbles are adsorbed and attached to the electrode surface and fluid channels for a long time, so that the noble metal catalytic active sites on the electrode surface are covered by gas, resulting in the loss of catalytic active sites and insufficient local supply of electrolyte, leading to high oxygen evolution overpotential, especially the overpotential at high current density is too high, making it difficult to increase the current density. Overall, the reduction in effective catalytic sites makes it difficult to reduce the loading amount of precious metals in the catalyst, making the electrode price per unit electrode area high, making it difficult for the electrolysis of water to produce hydrogen to be applied on a large scale in industry.
[0004] The existing means to solve the above problems mainly include constructing catalyst microstructures with different morphologies (such as leaf-shaped, needle-shaped, sheet-shaped, etc.), and adjusting the wettability of electrode materials through acid etching and loading of hydrophilic groups to regulate the bubble migration process on the electrode surface. However, the uneven distribution and disordered arrangement of catalysts with different morphologies on the electrode substrate will still lead to cross-coverage of effective active sites. The morphological characteristics and hydrophilicity of the catalysts are also difficult to control in a direction, resulting in the bubble management and induced migration on the electrode surface being still very difficult, and the coverage of active sites is still very serious. Therefore, there is an urgent need to design more efficient and effective bubble directional migration surfaces to prepare electrodes with high hydrogen evolution activity and stability. Summary of the invention
[0005] In order to solve the technical problem that bubble coverage leads to high electrode overpotential and difficulty in increasing current density during electrocatalytic hydrogen evolution, the present invention provides a preparation method and application of a dual-gradient self-supporting hydrogen evolution electrode. The preparation method of the present invention can reduce the accumulation of gas on the electrode surface, promote the in-situ separation of hydrogen on the electrode surface, thereby reducing the overpotential of the electrode at high current density, and at the same time, can also improve the stability of the electrode under long-term high current operation and reduce the overpotential growth rate.
[0006] The specific technical scheme of the present invention is: In a first aspect, the present invention provides a method for preparing a dual-gradient self-supporting hydrogen evolution electrode, comprising the following steps: S1: forming oxygen-containing hydrophilic groups on the surface of the conductive carbon cloth to obtain a pretreated carbon cloth; S2: In-situ self-growth of a metal organic framework composed of Co and dimethylimidazole on the surface of the pretreated carbon cloth, wherein the metal organic framework forms triangular protrusions on the surface of the pretreated carbon cloth, and calcination is performed to obtain a geometric gradient electrode; S3: Covering the surface of the geometric gradient electrode with a mask having a plurality of through holes, applying a hydrophobic and aerophilic coating on the surface of the geometric gradient electrode through the through holes, and forming a plurality of hydrophobic and aerophilic regions on the surface of the geometric gradient electrode.
[0007] The present invention adopts the above method to form a longitudinal (i.e., perpendicular to the electrode surface) geometric gradient and a transverse (i.e., parallel to the electrode surface) wetting gradient on the surface of the conductive carbon cloth. Specifically, after pretreatment, the conductive carbon cloth forms oxygen-containing hydrophilic groups on the surface, which can serve as nucleation sites for the organic metal skeleton. The free dimethylimidazole is coordinated and anchored on the surface of the carbon cloth. The organic coordination then self-assembles with cobalt metal ions to form a network topological structure. Subsequently, under the restriction of the crystal plane of water molecules, triangular protrusions grow perpendicular to the surface of the carbon cloth, i.e., a longitudinal geometric gradient is formed, and Co in the metal organic skeleton can play a catalytic role in electrocatalytic hydrogen evolution. After applying the hydrophobic and aerophilic coating, the area covered by the mask on the geometric gradient electrode surface is not applied with the hydrophobic and aerophilic coating, which is a hydrophilic and aerophilic area, and the area not covered by the template (i.e., the area corresponding to the through hole) is applied with the hydrophobic and aerophilic coating, which is a hydrophobic and aerophilic area. The hydrophilic and aerophilic areas adjacent to each other can form a transverse wetting gradient on the electrode surface.
[0008] The migration mechanism of water on the longitudinal geometric gradient is as follows: As the electrolysis current density increases, the surface of the triangular protrusions composed of the metal organic framework is gradually covered by bubbles. The difference in apparent contact angle will generate a shape gradient force acting on the droplet. The triangular protrusions have a structural gradient, which causes the liquid to produce an unbalanced surface tension on it. Due to the different contact areas, the apparent contact angles of the electrolyte droplets are different, which can guide the liquid to be transported from the tip of the triangle to the root of the catalyst under the action of the Laplace force, replenishing fresh electrolyte and hydrogen ions in water to the electrode surface, ensuring the stable existence of catalytic active sites at high current density, reducing the coverage time of bubbles on the hydrogen evolution catalytic active sites, and thus improving the efficiency of hydrogen production.
[0009] The migration mechanism of bubbles on the lateral wetting gradient is as follows: the hydrophilic and gas-repelling areas and the hydrophobic and gas-philic areas formed on the electrode surface by the mask can function as the electrolytic hydrogen decomposition area and the gas transport area, respectively. The hydrophilic and gas-repelling areas and the hydrophobic and gas-philic areas on the electrode surface form a wetting gradient on the interactive boundary. When bubbles are generated in the electrolytic hydrogen decomposition area, the bubbles will be affected by the gradient wetting gradient and move laterally from the electrolytic hydrogen decomposition area with a small bubble wetting angle to the gas-philic gas transport area under the action of surface tension, thereby ensuring that the catalytic active sites in the electrolytic hydrogen decomposition area under high current are not covered by bubbles, while also reducing the hydrogen partial pressure on its surface, so that the water electrolysis reaction proceeds in the forward direction, thus helping to improve the efficiency of hydrogen production.
[0010] In the above manner, by utilizing the longitudinal geometric gradient and the transverse wetting gradient of the electrode surface, the gas aggregation on the electrode surface can be reduced, and the in-situ separation of hydrogen on the electrode surface can be promoted, thereby reducing the overpotential of electrocatalytic hydrogen evolution (especially the overpotential under high current density). At the same time, the triangular protrusions are composed of a metal organic framework, which has an open porous structure, can expose more active sites, and are conducive to the active sites on the catalyst surface Full contact with the electrolyte, which can improve the intrinsic performance of the hydrogen evolution electrode and make the hydrogen evolution electrode have a lower overpotential.
[0011] In addition to being able to reduce the overpotential, the dual gradient of the electrode in the present invention can also control the growth process of the bubbles, and the bubble size can be reduced from more than 200 microns to 20 microns, which helps to reduce the impact of small bubble aggregation on the electrode surface, thereby reducing the possibility of catalyst shedding. In addition, the self-supporting synthesized catalyst of the present invention does not require the use of additional binders. These characteristics can ensure that the hydrogen evolution electrode operates stably under long-term high current and reduce the overpotential growth rate.
[0012] Preferably, in step S3, the through hole is in a triangular shape.
[0013] The triangular through-hole design enables the hydrophobic and aerophilic regions formed on the electrode surface to be triangular, which can form another geometric shape gradient. During the electrocatalytic hydrogen evolution process, when the tip of the triangular hydrophobic and aerophilic region is located below the electrolyte surface and the bottom is located above the electrolyte surface, the triangular shape gradient will help the bubbles to quickly migrate from the tip of the triangle to the space outside the electrolyte, thereby reducing the coverage of catalytic active sites in the electrocatalytic hydrogen evolution region under high current by bubbles to a greater extent, and reducing the hydrogen partial pressure on its surface, thereby further reducing the overpotential of the hydrogen evolution electrode.
[0014] Preferably, in step S3, the through hole has a top angle of 10° to 30°, a height of 10 to 20 mm, and a spacing of 100 to 200 μm between the bottom edges of adjacent through holes.
[0015] When the apex angle of the triangular through hole is too large, that is, the apex angle of the triangular hydrophobic and aerophilic area is too large, the Laplace force induced by the geometric effect will fail, and the directional transport of bubbles cannot be induced by the tip effect. Instead, the bubbles will accumulate inside the hydrophobic and aerophilic layer, resulting in excessive local hydrogen concentration, which is not conducive to the hydrogen evolution reaction.
[0016] Preferably, in step S3, the water wetting angle of the hydrophobic and aerophilic coating is less than 20°, and the total area of the hydrophobic and aerophilic regions accounts for 10-60% of the area of the electrode surface.
[0017] Preferably, in step S3, the hydrophobic and air-philic coating is composed of a polydimethylsiloxane layer and hydrophobic nano-SiO2 bonded to the polydimethylsiloxane layer.
[0018] Preferably, step S1 specifically comprises: washing the conductive carbon cloth with water and anhydrous ethanol and drying it, heating it to 450-550° C. at a rate of 10-15° C. / min and maintaining it for 2-5 h, and then washing it with water and ethanol.
[0019] Preferably, step S2 specifically comprises: preparing a mixture containing dimethylimidazole and Co 2+ The pretreated carbon cloth is suspended in the solution at an inclination angle of no more than 45° relative to the vertical direction, and is aged at 30-35°C for 2-5 h; the dimethylimidazole and Co 2+ The molar ratio of dimethylimidazole and Co is 1-12:1; 2+ In the solution, Co 2+ The concentration is 0.03~0.4mol / L.
[0020] Preferably, in step S2, the calcination process specifically comprises: heating to 550-650°C at a rate of 2-5°C / min and maintaining the temperature for 3-4 h.
[0021] Preferably, in step S3, the process of applying the hydrophobic and air-philic coating specifically includes: immersing the geometric gradient electrode covered with a mask in a solution containing a polydimethylsiloxane prepolymer and a curing agent for 10 to 100 s, taking it out and placing it in the air for 10 to 40 s to form a prepolymer layer; and then depositing hydrophobic nano-SiO2 on the prepolymer layer and curing it.
[0022] Furthermore, in the solution containing the polydimethylsiloxane prepolymer and the curing agent, the concentrations of the polydimethylsiloxane prepolymer and the curing agent are 0.6-0.9 g / mL and 0.1-0.4 g / mL, respectively.
[0023] Furthermore, the curing temperature is 80-100° C. and the curing time is 2-5 h.
[0024] Preferably, in step S3, the thickness of the mask is 10-200 μm.
[0025] In a second aspect, the present invention provides an application of a dual-gradient self-supporting hydrogen evolution electrode in electrocatalytic hydrogen evolution, wherein the dual-gradient self-supporting hydrogen evolution electrode is prepared by the above-mentioned preparation method.
[0026] Preferably, the dual-gradient self-supporting hydrogen evolution electrode is partially immersed in the electrolyte; the hydrophobic and aerophilic regions are triangular, and each hydrophobic and aerophilic region at the electrolyte surface has a bottom edge above the electrolyte surface and a top angle below the electrolyte surface.
[0027] Preferably, in the process of electrocatalytic hydrogen evolution, the dual-gradient self-supporting hydrogen evolution electrode is used as the working electrode cathode, the graphite rod electrode is used as the counter electrode, the Ag / AgCl electrode is used as the reference electrode, and the potassium hydroxide solution is used as the electrolyte.
[0028] Compared with the prior art, the present invention has the following advantages: (1) The present invention can reduce the gas accumulation on the electrode surface to a large extent and promote the in-situ separation of hydrogen on the electrode surface by constructing a longitudinal geometric gradient composed of a cobalt-based metal organic framework on the electrode surface, as well as a lateral wetting gradient composed of adjacent hydrophobic and aerophilic regions and hydrophilic and aerophobic regions, thereby effectively reducing the overpotential of the electrode at high current density. According to tests, the present invention can effectively reduce the overpotential of the electrode at 100 mA / cm2 when only non-precious metal Co is used as the catalytic metal. 2 The overpotential under current density can be as low as 80~87 mV, which is significantly lower than the conventional precious metal platinum carbon coated hydrogen evolution electrode (100~170mV). It not only effectively reduces the overpotential of the electrode under high current density, but also effectively reduces the raw material cost by avoiding the use of precious metals.
[0029] (2) The present invention can reduce the impact of small bubble coalescence on the electrode surface by constructing a longitudinal geometric gradient and a transverse wetting gradient on the electrode surface. The self-supporting synthesized catalyst of the present invention does not require the use of additional binders, thereby improving the stability of the electrode under long-term high current operation and reducing the overpotential growth rate. After testing, the hydrogen evolution electrode prepared by the present invention has a high conductivity at 100 mA / cm 2 At a current density of 1.3 Å, the overpotential increases by only 10 μV / h within 100 h, and the growth rate is only 10% of that of the conventional platinum-carbon electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is an electron microscope image of the surface of the hydrogen evolution electrode prepared in Example 1.
[0031] Figure 2Schematic diagram of the surface structure of the mask used in Example 1.
[0032] The reference numerals are: through hole 1 . DETAILED DESCRIPTION
[0033] The present invention will be further described below in conjunction with the embodiments.
[0034] A method for preparing a dual-gradient self-supporting hydrogen evolution electrode comprises the following steps: S1: forming oxygen-containing hydrophilic groups on the surface of the conductive carbon cloth to obtain a pretreated carbon cloth; S2: In-situ self-growth of a metal organic framework composed of Co and dimethylimidazole on the surface of the pretreated carbon cloth, wherein the metal organic framework forms triangular protrusions on the surface of the pretreated carbon cloth, and calcination is performed to obtain a geometric gradient electrode; S3: Covering the surface of the geometric gradient electrode with a mask having a plurality of through holes, applying a hydrophobic and aerophilic coating on the surface of the geometric gradient electrode through the through holes, and forming a plurality of hydrophobic and aerophilic regions on the surface of the geometric gradient electrode.
[0035] In some specific embodiments, step S1 specifically includes: washing the conductive carbon cloth with water and anhydrous ethanol and drying it, heating it to 450-550° C. at a rate of 10-15° C. / min and maintaining it for 2-5 h, and then washing it with water and ethanol.
[0036] In some specific embodiments, step S2 specifically comprises: preparing a mixture containing dimethylimidazole and Co 2+ The pretreated carbon cloth is suspended in the solution at an inclination angle of no more than 45° relative to the vertical direction, and is aged at 30-35°C for 2-5 hours; the dimethylimidazole and Co 2+ The molar ratio of dimethylimidazole and Co is 1-12:1; 2+ In the solution, Co 2+ The concentration is 0.03~0.4 mol / L.
[0037] In some specific embodiments, in step S2, the calcination process specifically includes: heating to 550-650° C. at a rate of 2-5° C. / min and maintaining for 3-4 h.
[0038] In some specific embodiments, in step S3, the through hole is in a triangular shape with a vertex angle of 10° to 30° and a height of 10 to 20 mm, and the interval between the bottom sides of adjacent through holes is 100 to 200 μm.
[0039] In some specific implementations, in step S3, the thickness of the mask is 10-200 μm.
[0040] In some specific embodiments, in step S3, the water wetting angle of the hydrophobic and aerophilic coating is less than 20°, and the total area of the hydrophobic and aerophilic regions accounts for 10-60% of the area of the electrode surface.
[0041] In some specific embodiments, in step S3, the hydrophobic and air-philic coating is composed of a polydimethylsiloxane layer and hydrophobic nano-SiO2 bonded to the polydimethylsiloxane layer.
[0042] In some specific embodiments, in step S3, the process of applying the hydrophobic and air-philic coating specifically includes: soaking the geometric gradient electrode covered with a mask in a solution containing 0.6~0.9 g / mL polydimethylsiloxane prepolymer and 0.1~0.4 g / mL curing agent for 10~100 s, taking it out and placing it in the air for 10~40 s to form a prepolymer layer; then depositing hydrophobic nano-SiO2 on the prepolymer layer and curing it at 80~100°C for 2~5 h.
[0043] A dual-gradient self-supporting hydrogen evolution electrode is used in electrocatalytic hydrogen evolution. The dual-gradient self-supporting hydrogen evolution electrode is prepared by the above-mentioned preparation method.
[0044] In some specific embodiments, the dual-gradient self-supporting hydrogen evolution electrode is partially immersed in the electrolyte; the hydrophobic and aerophilic regions are triangular, and the bottom edge of each hydrophobic and aerophilic region at the electrolyte surface is located above the electrolyte surface, and the top angle is located below the electrolyte surface.
[0045] In some specific embodiments, during the electrocatalytic hydrogen evolution process, the dual-gradient self-supporting hydrogen evolution electrode is used as the working electrode cathode, the graphite rod electrode is used as the counter electrode, the Ag / AgCl electrode is used as the reference electrode, and the potassium hydroxide solution is used as the electrolyte.
[0046] The present invention is described below by specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Without departing from the spirit and scope of the inventive concept, changes and advantages that can be thought of by those skilled in the art are included in the present invention, and the attached claims and any equivalents thereof are the protection scope of the present invention.
[0047] Example 1 The steps of preparing the hydrogen evolution electrode in this embodiment are as follows: (1) Select a 4 cm 2 The flexible conductive carbon cloth was washed alternately with deionized water and anhydrous ethanol for three times and then dried in a vacuum oven for 24 h.
[0048] (2) The dried carbon cloth was heated to 450°C in a muffle furnace at a heating rate of 10°C / min and heated at this temperature for 3 h. It was then washed alternately with deionized water and anhydrous ethanol for 3 times and then dried in a vacuum oven overnight to obtain a pretreated carbon cloth.
[0049] (3) Add dimethylimidazole to deionized water and sonicate for 45 min to fully dissolve it, to prepare 50 mL of dimethylimidazole solution with a concentration of 0.4 mol / L; add Co(NO3)2·6H2O to deionized water and sonicate for 45 min to fully dissolve it, to prepare 50 mL of cobalt nitrate solution with a concentration of 0.08 mol / L.
[0050] (4) Pour the prepared cobalt nitrate solution into the dimethylimidazole solution quickly and stir at a stirring speed of 50 r / min for 1 min to fully mix the solutions to obtain a mixed solution.
[0051] (5) The pretreated carbon cloth was vertically suspended in the mixed solution and placed in a constant temperature box at 30°C for 5 h of aging, so that the triangular sheet-like two-dimensional cobalt-based organic metal framework (Co-MOF) catalyst grew in situ on the surface of the carbon cloth, forming triangular protrusions extending from the electrode catalyst substrate. Subsequently, the carbon cloth was heated to 550°C at a heating rate of 2°C / min in a tubular furnace under the protection of argon gas and annealed for 3 h to obtain a geometric gradient electrode.
[0052] (6) Take a PET plastic mask with a thickness of 10 μm, which is slightly larger than the size of the carbon cloth, and cut triangular through holes by laser. The vertex angle of the triangular through holes is 10°, the height is 20 mm, and the base interval of adjacent triangular through holes is 200 μm (the arrangement of triangular through holes in the mask is shown in Figure 2 , that is: a row of triangular through holes 1 are arranged on the mask, each triangular through hole has the same shape and direction, and there is a gap between adjacent triangular through holes), and then the mask is clamped to cover the front and back surfaces of the geometric gradient electrode.
[0053] (7) Dissolve 1.0 g of polydimethylsiloxane (PDMS) prepolymer containing 10 wt% curing agent (Dow Corning DC184 PDMS polydimethylsiloxane high transparency curing agent) in 10 mL of n-hexane and stir thoroughly to prepare a dipping solution. Immerse the geometric gradient electrode covered with a mask in the dipping solution for 15 s, take it out and place it in room temperature air for 30 s to allow a layer of PDMS prepolymer to adhere to the electrode surface.
[0054] (8) The hydrophobic nano-SiO2 particles (average particle size 16 nm) were uniformly deposited on the electrode surface with the PDMS prepolymer layer. The PDMS prepolymer layer was cured by heating at 80°C for 2 h, while the hydrophobic nano-SiO2 particles were tightly attached. The surface was then carefully rinsed with sufficient ethanol to remove the unbound hydrophobic nano-SiO2 particles, and then dried under a nitrogen flow for 24 h.
[0055] (9) The PET plastic mask sandwiched between the front and back sides of the electrode was removed to obtain a hydrogen evolution electrode. On the surface of the hydrogen evolution electrode, the area covered by the mask was attached with hydrophobic nano-SiO2 particles, which was a hydrophilic and aerophilic area. The adjacent mask gap area was a hydrophobic and aerophilic area, forming a lateral wetting gradient. The water wetting angle of the hydrophobic and aerophilic area was 16°, and the total area of the hydrophobic and aerophilic area accounted for 43% of the area of the electrode surface.
[0056] The surface structure of the hydrogen evolution electrode prepared in this embodiment is as follows: Figure 1 shown.
[0057] Example 2 The steps of preparing the hydrogen evolution electrode in this embodiment are as follows: (1) Select a 8 cm 2 The flexible conductive carbon cloth was washed alternately with deionized water and anhydrous ethanol for 4 times and then dried in a vacuum oven for 36 h.
[0058] (2) The dried carbon cloth was heated to 500°C in a muffle furnace at a heating rate of 12°C / min and heated at this temperature for 3 h. It was then washed alternately with deionized water and anhydrous ethanol for 4 times and then dried in a vacuum oven overnight to obtain a pretreated carbon cloth.
[0059] (3) Add dimethylimidazole to deionized water and sonicate for 45 min to fully dissolve it, to prepare 50 mL of dimethylimidazole solution with a concentration of 0.4 mol / L; add Co(NO3)2·6H2O to deionized water and sonicate for 45 min to fully dissolve it, to prepare 50 mL of cobalt nitrate solution with a concentration of 0.08 mol / L.
[0060] (4) Pour the prepared cobalt nitrate solution into the dimethylimidazole solution quickly and stir at a stirring speed of 100 r / min for 1.5 min to fully mix the solutions to obtain a mixed solution.
[0061] (5) The pretreated carbon cloth was vertically suspended in the mixed solution and placed in a constant temperature box at 35°C for 3 h of aging, so that the triangular sheet-like two-dimensional cobalt-based organic metal framework (Co-MOF) catalyst grew in situ on the surface of the carbon cloth, forming triangular protrusions extending from the electrode catalyst substrate. Subsequently, it was heated to 500°C at a heating rate of 4°C / min in a tubular furnace under the protection of argon gas and annealed for 3.5 h to obtain a geometric gradient electrode.
[0062] (6) Take a PET plastic mask with a thickness of 10 μm, which is slightly larger than the size of the carbon cloth, and cut triangular through holes by laser. The vertex angle of the triangular through holes is 20°, the height is 20 mm, and the base interval of adjacent triangular through holes is 150 μm (the arrangement of the triangular through holes in the mask is the same as in Example 1, and the only difference from Example 1 is the through hole size and interval). Then, clamp the mask to cover the front and back surfaces of the geometric gradient electrode.
[0063] (7) Dissolve 1.0 g of polydimethylsiloxane (PDMS) prepolymer containing 10 wt% curing agent (Dow Corning DC184 PDMS polydimethylsiloxane high transparency curing agent) in 10 mL of n-hexane and stir thoroughly to prepare a dipping solution. Immerse the geometric gradient electrode covered with a mask in the dipping solution for 60 s, take it out and place it in room temperature air for 30 s to allow a layer of PDMS prepolymer to adhere to the electrode surface.
[0064] (8) The hydrophobic nano-SiO2 particles (average particle size 16 nm) were uniformly deposited on the electrode surface with the PDMS prepolymer layer. The PDMS prepolymer layer was cured by heating at 85°C for 3 h, and the hydrophobic nano-SiO2 particles were tightly attached. The surface was then carefully rinsed with sufficient ethanol to remove the unbound hydrophobic nano-SiO2 particles, and then dried under a nitrogen flow for 24 h.
[0065] (9) The PET plastic mask sandwiched between the front and back sides of the electrode was removed to obtain a hydrogen evolution electrode. On the surface of the hydrogen evolution electrode, the area covered by the mask was attached with hydrophobic nano-SiO2 particles, which was a hydrophilic and aerophilic area. The adjacent mask gap area was a hydrophobic and aerophilic area, forming a lateral wetting gradient. The water wetting angle of the hydrophobic and aerophilic area was 12°, and the total area of the hydrophobic and aerophilic area accounted for 58% of the area of the electrode surface.
[0066] Example 3 The steps of preparing the hydrogen evolution electrode in this embodiment are as follows: (1) Select a 16 cm 2 The flexible conductive carbon cloth was washed alternately with deionized water and anhydrous ethanol for 6 times and then dried in a vacuum oven for 48 h.
[0067] (2) The dried carbon cloth was heated to 550°C in a muffle furnace at a heating rate of 15°C / min and heated at this temperature for 5 h. It was then washed alternately with deionized water and anhydrous ethanol for 6 times and then dried in a vacuum oven overnight to obtain a pretreated carbon cloth.
[0068] (3) Add dimethylimidazole to deionized water and sonicate for 45 min to fully dissolve it, to prepare 50 mL of dimethylimidazole solution with a concentration of 0.4 mol / L; add Co(NO3)2·6H2O to deionized water and sonicate for 45 min to fully dissolve it, to prepare 50 mL of cobalt nitrate solution with a concentration of 0.08 mol / L.
[0069] (4) Pour the prepared cobalt nitrate solution into the dimethylimidazole solution quickly and stir at a stirring speed of 200 r / min for 3 min to fully mix the solutions to obtain a mixed solution.
[0070] (5) The pretreated carbon cloth was vertically suspended in the mixed solution and placed in a constant temperature box at 35°C for 5 h of aging, so that the triangular sheet-like two-dimensional cobalt-based organic metal framework (Co-MOF) catalyst grew in situ on the surface of the carbon cloth, forming triangular protrusions extending from the electrode catalyst substrate. Subsequently, it was heated to 650°C at a heating rate of 5°C / min in a tubular furnace under the protection of argon gas and annealed for 4 h to obtain a geometric gradient electrode.
[0071] (6) Take a PET plastic mask with a thickness of 10 μm, which is slightly larger than the size of the carbon cloth, and cut triangular through holes by laser. The vertex angle of the triangular through holes is 30°, the height is 20 mm, and the base interval of adjacent triangular through holes is 200 μm (the arrangement of the triangular through holes in the mask is the same as in Example 1, and the only difference from Example 1 is the through hole size and interval). Then, clamp the mask to cover the front and back surfaces of the geometric gradient electrode.
[0072] (7) Dissolve 1.0 g of polydimethylsiloxane (PDMS) prepolymer containing 10 wt% curing agent (Dow Corning DC184 PDMS polydimethylsiloxane high transparency curing agent) in 10 mL of n-hexane and stir thoroughly to prepare a dipping solution. Immerse the geometric gradient electrode covered with a mask in the dipping solution for 100 s, take it out and place it in room temperature air for 40 s to allow a layer of PDMS prepolymer to adhere to the electrode surface.
[0073] (8) The hydrophobic nano-SiO2 particles (average particle size 16 nm) were uniformly deposited on the electrode surface with the PDMS prepolymer layer. The PDMS prepolymer layer was cured by heating at 100°C for 5 h, and the hydrophobic nano-SiO2 particles were tightly attached. The surface was then carefully rinsed with sufficient ethanol to remove the unbound hydrophobic nano-SiO2 particles, and then dried under a nitrogen flow for 24 h.
[0074] (9) The PET plastic mask sandwiched between the front and back sides of the electrode was removed to obtain a hydrogen evolution electrode. On the surface of the hydrogen evolution electrode, the area covered by the mask was attached with hydrophobic nano-SiO2 particles, which was a hydrophilic and aerophilic area. The adjacent mask gap area was a hydrophobic and aerophilic area, forming a lateral wetting gradient. The water wetting angle of the hydrophobic and aerophilic area was 15°, and the total area of the hydrophobic and aerophilic area accounted for 60% of the area of the electrode surface.
[0075] Comparative Example 1 This comparative example is a conventional platinum carbon electrode.
[0076] Comparative Example 2 The difference between this comparative example and Example 1 is that this comparative example does not construct a lateral wetting gradient on the electrode surface, that is, steps (6) to (9) are not performed. Specifically, the steps for preparing the hydrogen evolution electrode in this comparative example are as follows: (1) Select a 4 cm 2 The flexible conductive carbon cloth was washed alternately with deionized water and anhydrous ethanol for three times and then dried in a vacuum oven for 24 h.
[0077] (2) The dried carbon cloth was heated to 450°C in a muffle furnace at a heating rate of 10°C / min and heated at this temperature for 3 h. It was then washed alternately with deionized water and anhydrous ethanol for 3 times and then dried in a vacuum oven overnight to obtain a pretreated carbon cloth.
[0078] (3) Add dimethylimidazole to deionized water and sonicate for 45 min to fully dissolve it, to prepare 50 mL of dimethylimidazole solution with a concentration of 0.4 mol / L; add Co(NO3)2·6H2O to deionized water and sonicate for 45 min to fully dissolve it, to prepare 50 mL of cobalt nitrate solution with a concentration of 0.08 mol / L.
[0079] (4) Pour the prepared cobalt nitrate solution into the dimethylimidazole solution quickly and stir at a stirring speed of 50 r / min for 1 min to fully mix the solutions to obtain a mixed solution.
[0080] (5) The pretreated carbon cloth was vertically suspended in the mixed solution and placed in a constant temperature box at 30°C for 5 h of aging, so that the triangular sheet-like two-dimensional cobalt-based organic metal framework (Co-MOF) catalyst grew in situ on the surface of the carbon cloth, forming triangular protrusions extending from the electrode catalyst substrate. Subsequently, the carbon cloth was heated to 550°C at a heating rate of 2°C / min in a tubular furnace under the protection of argon gas and annealed for 3 h to obtain a hydrogen evolution electrode.
[0081] Comparative Example 3 The difference between this comparative example and Example 1 is that the through hole shape in the mask used in this comparative example is a straight line. Specifically, the steps for preparing the hydrogen evolution electrode in this comparative example are as follows: (1) Select a 4 cm 2 The flexible conductive carbon cloth was washed alternately with deionized water and anhydrous ethanol for three times and then dried in a vacuum oven for 24 h.
[0082] (2) The dried carbon cloth was heated to 450°C in a muffle furnace at a heating rate of 10°C / min and heated at this temperature for 3 h. It was then washed alternately with deionized water and anhydrous ethanol for 3 times and then dried in a vacuum oven overnight to obtain a pretreated carbon cloth.
[0083] (3) Add dimethylimidazole to deionized water and sonicate for 45 min to fully dissolve it, to prepare 50 mL of dimethylimidazole solution with a concentration of 0.4 mol / L; add Co(NO3)2·6H2O to deionized water and sonicate for 45 min to fully dissolve it, to prepare 50 mL of cobalt nitrate solution with a concentration of 0.08 mol / L.
[0084] (4) Pour the prepared cobalt nitrate solution into the dimethylimidazole solution quickly and stir at a stirring speed of 50 r / min for 1 min to fully mix the solutions to obtain a mixed solution.
[0085] (5) The pretreated carbon cloth was vertically suspended in the mixed solution and placed in a constant temperature box at 30°C for 5 h of aging, so that the triangular sheet-like two-dimensional cobalt-based organic metal framework (Co-MOF) catalyst grew in situ on the surface of the carbon cloth, forming triangular protrusions extending from the electrode catalyst substrate. Subsequently, the carbon cloth was heated to 550°C at a heating rate of 2°C / min in a tubular furnace under the protection of argon gas and annealed for 3 h to obtain a geometric gradient electrode.
[0086] (6) Take a PET plastic mask with a thickness of 10 μm, which is slightly larger than the size of the carbon cloth. Use laser to cut vertical and parallel straight through holes. The width of the straight through holes is 640 μm, and the interval between adjacent through holes is 1000 μm. Then clamp the mask to cover the front and back surfaces of the geometric gradient electrode.
[0087] (7) Dissolve 1.0 g of polydimethylsiloxane (PDMS) prepolymer containing 10 wt% curing agent (Dow Corning DC184 PDMS polydimethylsiloxane high transparency curing agent) in 10 mL of n-hexane and stir thoroughly to prepare a dipping solution. Immerse the geometric gradient electrode covered with a mask in the dipping solution for 15 s, take it out and place it in room temperature air for 30 s to allow a layer of PDMS prepolymer to adhere to the electrode surface.
[0088] (8) The hydrophobic nano-SiO2 particles (average particle size 16 nm) were uniformly deposited on the electrode surface with the PDMS prepolymer layer. The PDMS prepolymer layer was cured by heating at 80°C for 2 h, while the hydrophobic nano-SiO2 particles were tightly attached. The surface was then carefully rinsed with sufficient ethanol to remove the unbound hydrophobic nano-SiO2 particles, and then dried under a nitrogen flow for 24 h.
[0089] (9) The PET plastic mask sandwiched between the front and back sides of the electrode was removed to obtain a hydrogen evolution electrode. On the surface of the hydrogen evolution electrode, the area covered by the mask was attached with hydrophobic nano-SiO2 particles, which was a hydrophilic and aerophilic area. The adjacent mask gap area was a hydrophobic and aerophilic area, forming a lateral wetting gradient. The water wetting angle of the hydrophobic and aerophilic area was 16°, and the total area of the hydrophobic and aerophilic area accounted for 43% of the area of the electrode surface.
[0090] Comparative Example 4 The difference between this comparative example and Example 1 is that the through hole in the mask used in this comparative example is circular in shape. Specifically, the steps for preparing the hydrogen evolution electrode in this comparative example are as follows: (1) Select a 4 cm 2 The flexible conductive carbon cloth was washed alternately with deionized water and anhydrous ethanol for three times and then dried in a vacuum oven for 24 h.
[0091] (2) The dried carbon cloth was heated to 450°C in a muffle furnace at a heating rate of 10°C / min and heated at this temperature for 3 h. It was then washed alternately with deionized water and anhydrous ethanol for 3 times and then dried in a vacuum oven overnight to obtain a pretreated carbon cloth.
[0092] (3) Add dimethylimidazole to deionized water and sonicate for 45 min to fully dissolve it, to prepare 50 mL of dimethylimidazole solution with a concentration of 0.4 mol / L; add Co(NO3)2·6H2O to deionized water and sonicate for 45 min to fully dissolve it, to prepare 50 mL of cobalt nitrate solution with a concentration of 0.08 mol / L.
[0093] (4) Pour the prepared cobalt nitrate solution into the dimethylimidazole solution quickly and stir at a stirring speed of 50 r / min for 1 min to fully mix the solutions to obtain a mixed solution.
[0094] (5) The pretreated carbon cloth was vertically suspended in the mixed solution and placed in a constant temperature box at 30°C for 5 h of aging, so that the triangular sheet-like two-dimensional cobalt-based organic metal framework (Co-MOF) catalyst grew in situ on the surface of the carbon cloth, forming triangular protrusions extending from the electrode catalyst substrate. Subsequently, the carbon cloth was heated to 550°C at a heating rate of 2°C / min in a tubular furnace under the protection of argon gas and annealed for 3 h to obtain a geometric gradient electrode.
[0095] (6) Take a PET plastic mask with a thickness of 10 μm, which is slightly larger than the size of the carbon cloth, and cut circular through holes by laser. The diameter of the circular through holes is 400 μm, and the interval between adjacent through holes is 1000 μm (the arrangement of the circular through holes in the mask is the same as in Example 1). Then, clamp the mask to cover the front and back surfaces of the geometric gradient electrode.
[0096] (7) Dissolve 1.0 g of polydimethylsiloxane (PDMS) prepolymer containing 10 wt% curing agent (Dow Corning DC184 PDMS polydimethylsiloxane high transparency curing agent) in 10 mL of n-hexane and stir thoroughly to prepare a dipping solution. Immerse the geometric gradient electrode covered with a mask in the dipping solution for 15 s, take it out and place it in room temperature air for 30 s to allow a layer of PDMS prepolymer to adhere to the electrode surface.
[0097] (8) The hydrophobic nano-SiO2 particles (average particle size 16 nm) were uniformly deposited on the electrode surface with the PDMS prepolymer layer. The PDMS prepolymer layer was cured by heating at 80°C for 2 h, while the hydrophobic nano-SiO2 particles were tightly attached. The surface was then carefully rinsed with sufficient ethanol to remove the unbound hydrophobic nano-SiO2 particles, and then dried under a nitrogen flow for 24 h.
[0098] (9) The PET plastic mask sandwiched between the front and back sides of the electrode was removed to obtain a hydrogen evolution electrode. On the surface of the hydrogen evolution electrode, the area covered by the mask was attached with hydrophobic nano-SiO2 particles, which was a hydrophilic and aerophilic area. The adjacent mask gap area was a hydrophobic and aerophilic area, forming a lateral wetting gradient. The water wetting angle of the hydrophobic and aerophilic area was 16°, and the total area of the hydrophobic and aerophilic area accounted for 43% of the area of the electrode surface.
[0099] Comparative Example 5 The difference between this comparative example and Example 1 is that the top angle of the through hole in the mask used in this comparative example is 5°. Specifically, the steps for preparing the hydrogen evolution electrode in this comparative example are as follows: (1) Select a 4 cm2 The flexible conductive carbon cloth was washed alternately with deionized water and anhydrous ethanol for three times and then dried in a vacuum oven for 24 h.
[0100] (2) The dried carbon cloth was heated to 450°C in a muffle furnace at a heating rate of 10°C / min and heated at this temperature for 3 h. It was then washed alternately with deionized water and anhydrous ethanol for 3 times and then dried in a vacuum oven overnight to obtain a pretreated carbon cloth.
[0101] (3) Add dimethylimidazole to deionized water and sonicate for 45 min to fully dissolve it, to prepare 50 mL of dimethylimidazole solution with a concentration of 0.4 mol / L; add Co(NO3)2·6H2O to deionized water and sonicate for 45 min to fully dissolve it, to prepare 50 mL of cobalt nitrate solution with a concentration of 0.08 mol / L.
[0102] (4) Pour the prepared cobalt nitrate solution into the dimethylimidazole solution quickly and stir at a stirring speed of 50 r / min for 1 min to fully mix the solutions to obtain a mixed solution.
[0103] (5) The pretreated carbon cloth was vertically suspended in the mixed solution and placed in a constant temperature box at 30°C for 5 h of aging, so that the triangular sheet-like two-dimensional cobalt-based organic metal framework (Co-MOF) catalyst grew in situ on the surface of the carbon cloth, forming triangular protrusions extending from the electrode catalyst substrate. Subsequently, the carbon cloth was heated to 550°C at a heating rate of 2°C / min in a tubular furnace under the protection of argon gas and annealed for 3 h to obtain a geometric gradient electrode.
[0104] (6) Take a PET plastic mask with a thickness of 10 μm, which is slightly larger than the size of the carbon cloth, and cut triangular through holes by laser. The vertex angle of the triangular through holes is 5° and the height is 20 mm (the arrangement of the triangular through holes in the mask is the same as in Example 1). Then, clamp the mask to cover the front and back surfaces of the geometric gradient electrode.
[0105] (7) Dissolve 1.0 g of polydimethylsiloxane (PDMS) prepolymer containing 10 wt% curing agent (Dow Corning DC184 PDMS polydimethylsiloxane high transparency curing agent) in 10 mL of n-hexane and stir thoroughly to prepare a dipping solution. Immerse the geometric gradient electrode covered with a mask in the dipping solution for 15 s, take it out and place it in room temperature air for 30 s to allow a layer of PDMS prepolymer to adhere to the electrode surface.
[0106] (8) The hydrophobic nano-SiO2 particles (average particle size 16 nm) were uniformly deposited on the electrode surface with the PDMS prepolymer layer. The PDMS prepolymer layer was cured by heating at 80°C for 2 h, while the hydrophobic nano-SiO2 particles were tightly attached. The surface was then carefully rinsed with sufficient ethanol to remove the unbound hydrophobic nano-SiO2 particles, and then dried under a nitrogen flow for 24 h.
[0107] (9) The PET plastic mask sandwiched between the front and back sides of the electrode was removed to obtain a hydrogen evolution electrode. On the surface of the hydrogen evolution electrode, the area covered by the mask was attached with hydrophobic nano-SiO2 particles, which was a hydrophilic and aerophilic area. The adjacent mask gap area was a hydrophobic and aerophilic area, forming a lateral wetting gradient. The water wetting angle of the hydrophobic and aerophilic area was 16°, and the area of the hydrophobic and aerophilic area accounted for 43% of the electrode surface.
[0108] Comparative Example 6 The difference between this comparative example and Example 1 is that the top angle of the through hole in the mask used in this comparative example is 60°. Specifically, the steps for preparing the hydrogen evolution electrode in this comparative example are as follows: (1) Select a 4 cm 2 The flexible conductive carbon cloth was washed alternately with deionized water and anhydrous ethanol for three times and then dried in a vacuum oven for 24 h.
[0109] (2) The dried carbon cloth was heated to 450°C in a muffle furnace at a heating rate of 10°C / min and heated at this temperature for 3 h. It was then washed alternately with deionized water and anhydrous ethanol for 3 times and then dried in a vacuum oven overnight to obtain a pretreated carbon cloth.
[0110] (3) Add dimethylimidazole to deionized water and sonicate for 45 min to fully dissolve it, to prepare 50 mL of dimethylimidazole solution with a concentration of 0.4 mol / L; add Co(NO3)2·6H2O to deionized water and sonicate for 45 min to fully dissolve it, to prepare 50 mL of cobalt nitrate solution with a concentration of 0.08 mol / L.
[0111] (4) Pour the prepared cobalt nitrate solution into the dimethylimidazole solution quickly and stir at a stirring speed of 50 r / min for 1 min to fully mix the solutions to obtain a mixed solution.
[0112] (5) The pretreated carbon cloth was vertically suspended in the mixed solution and placed in a constant temperature box at 30°C for 5 h of aging, so that the triangular sheet-like two-dimensional cobalt-based organic metal framework (Co-MOF) catalyst grew in situ on the surface of the carbon cloth, forming triangular protrusions extending from the electrode catalyst substrate. Subsequently, the carbon cloth was heated to 550°C at a heating rate of 2°C / min in a tubular furnace under the protection of argon gas and annealed for 3 h to obtain a geometric gradient electrode.
[0113] (6) Take a PET plastic mask with a thickness of 10 μm, which is slightly larger than the size of the carbon cloth, and cut triangular through holes by laser. The vertex angle of the triangular through holes is 40° and the height is 20 mm (the arrangement of the triangular through holes in the mask is the same as in Example 1). Then, clamp the mask to cover the front and back surfaces of the geometric gradient electrode.
[0114] (7) Dissolve 1.0 g of polydimethylsiloxane (PDMS) prepolymer containing 10 wt% curing agent (Dow Corning DC184 PDMS polydimethylsiloxane high transparency curing agent) in 10 mL of n-hexane and stir thoroughly to prepare a dipping solution. Immerse the geometric gradient electrode covered with a mask in the dipping solution for 15 s, take it out and place it in room temperature air for 30 s to allow a layer of PDMS prepolymer to adhere to the electrode surface.
[0115] (8) The hydrophobic nano-SiO2 particles (average particle size 16 nm) were uniformly deposited on the electrode surface with the PDMS prepolymer layer. The PDMS prepolymer layer was cured by heating at 80°C for 2 h, while the hydrophobic nano-SiO2 particles were tightly attached. The surface was then carefully rinsed with sufficient ethanol to remove the unbound hydrophobic nano-SiO2 particles, and then dried under a nitrogen flow for 24 h.
[0116] (9) The PET plastic mask sandwiched between the front and back sides of the electrode was removed to obtain a hydrogen evolution electrode. On the surface of the hydrogen evolution electrode, the area covered by the mask was attached with hydrophobic nano-SiO2 particles, which was a hydrophilic and aerophilic area. The adjacent mask gap area was a hydrophobic and aerophilic area, forming a lateral wetting gradient. The water wetting angle of the hydrophobic and aerophilic area was 16°, and the area of the hydrophobic and aerophilic area accounted for 43% of the electrode surface.
[0117] Application Examples A single-chamber three-electrode system electrolyzer was assembled. In the electrolyzer, the hydrogen evolution electrodes prepared in the embodiments and comparative examples were respectively used as the working electrode cathode. When the hydrogen evolution electrodes in embodiments 1 to 3 and comparative examples 5 and 6 were used, the bottom edge of each hydrophobic aerophilic region at the electrolyte surface was 2 mm higher than the electrolyte surface; when the hydrogen evolution electrode in comparative example 3 was used, the upper edge of each hydrophobic aerophilic region at the electrolyte surface was 2 mm higher than the electrolyte surface; when the hydrogen evolution electrode in comparative example 4 was used, the upper edge of each hydrophobic aerophilic region at the electrolyte surface was 40 μm higher than the electrolyte surface. A standard Ag / AgCl electrode was used as a reference electrode, a graphite rod electrode was used as a counter electrode, a potassium hydroxide solution with a concentration of 1 mol / L was injected into the electrolyzer as an electrolyte, the pH value was adjusted to 14, and an electrolytic hydrogen evolution reaction was performed.
[0118] At 100 mA / cm 2At a current density of 1.5 , a constant current test was performed, the overpotential was recorded at 0 h, and the overpotential was recorded again at 100 h, and the overpotential growth rate was calculated. The results are shown in Table 1. The calculation formula for the overpotential growth rate is as follows: overpotential growth rate = (overpotential at 100 h - overpotential at 0 h) / 100 h.
[0119] Table 1 Hydrogen evolution electrode performance test results
[0120] Test result analysis: (1) By comparing Examples 1 to 3 with Comparative Example 1, it can be seen that, compared with the conventional platinum-carbon electrode, the method of the present invention can effectively reduce the overpotential and overpotential growth rate of the hydrogen evolution electrode.
[0121] (2) By comparing Example 1 with Comparative Example 2, it can be seen that the present invention uses a mask to form a lateral wetting gradient on the electrode surface, which can reduce the overpotential and overpotential growth rate of the hydrogen evolution electrode. The reason for this is that the hydrophilic and gas-repelling areas and the hydrophobic and gas-philic areas formed on the electrode surface by using the mask can function as the electrolytic hydrogen evolution area and the gas transport area respectively; the hydrophilic and gas-repelling areas and the hydrophobic and gas-philic areas on the electrode surface form a wetting gradient on the interactive boundaries; when bubbles are generated in the electrolytic hydrogen evolution area, the bubbles will be affected by the gradient wetting gradient, and under the action of surface tension, they will move laterally from the electrolytic hydrogen evolution area with a small bubble wetting angle to the gas-philic gas transport area, thereby ensuring that the catalytic active sites in the electrolytic hydrogen evolution area under high current are not covered by bubbles, and at the same time, the hydrogen partial pressure on its surface is reduced, so that the water electrolysis reaction proceeds in the forward direction, thereby helping to improve the hydrogen generation efficiency and reduce the impact of the small bubble aggregation process on the electrode surface.
[0122] (3) Comparing Example 1 with Comparative Examples 3 and 4, it can be seen that: compared with the straight and circular shapes, the present invention designs the shape of the through hole on the mask to be triangular, which is beneficial to reducing the overpotential and overpotential growth rate of the hydrogen evolution electrode. The reason for this is that the hydrophobic and aerophilic area formed by the triangular through hole can form a geometric shape gradient, thereby effectively inducing the migration of bubbles from the tip to the bottom, which is beneficial to the transfer of bubbles in the hydrophilic and aerophilic area to the hydrophobic and aerophilic area; while the hydrophobic and aerophilic area formed by the straight through hole lacks unbalanced surface tension, and the directional transport of bubbles will be restricted, so the effect of reducing the overpotential and overpotential growth rate is poor; the hydrophobic and aerophilic area formed by the circular through hole is difficult to induce bubbles to be sent to the external space of the electrolyte, and they gather on the electrode surface, and the directional transport of bubbles cannot be achieved.
[0123] (4) By comparing Example 1 with Comparative Example 6, it can be seen that when the vertex angle of the triangular through hole is too large, the overpotential and overpotential growth rate of the hydrogen evolution electrode will be large. The reason for this is that when the vertex angle of the triangular through hole is too large, the vertex angle of the triangular hydrophobic and aerophilic region formed is too large, which will cause the Laplace force induced by the geometric effect to fail, and the directional transport of bubbles cannot be induced by the tip effect. Instead, bubbles are accumulated inside the hydrophobic and aerophilic layer, resulting in excessively high local hydrogen concentration.
[0124] Unless otherwise defined, all technical terms and scientific terms used in the present invention have the same meanings as those commonly understood by ordinary technicians in the field to which the present disclosure belongs. Unless otherwise specified, the raw materials and equipment used in the present invention are conventional raw materials and equipment in the field and can be obtained from conventional commercial channels; unless otherwise specified, the methods used in the present invention are conventional methods in the field.
[0125] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a dual-gradient self-supporting hydrogen evolution electrode, characterized in that: The following steps are involved: S1: forming oxygen-containing hydrophilic groups on the surface of the conductive carbon cloth to obtain a pretreated carbon cloth; S2: In-situ self-growth of a metal organic framework composed of Co and dimethylimidazole on the surface of the pretreated carbon cloth, wherein the metal organic framework forms triangular protrusions on the surface of the pretreated carbon cloth, and calcination is performed to obtain a geometric gradient electrode; S3: Covering the surface of the geometric gradient electrode with a mask having a plurality of through holes, applying a hydrophobic and aerophilic coating on the surface of the geometric gradient electrode through the through holes, and forming a plurality of hydrophobic and aerophilic regions on the surface of the geometric gradient electrode.
2. The preparation method according to claim 1, characterized in that: In step S3, the through hole is in a triangular shape.
3. The preparation method according to claim 2, characterized in that: In step S3, the through holes have a top angle of 10° to 30°, a height of 10 to 20 mm, and a spacing of 100 to 200 μm between the bottom edges of adjacent through holes.
4. The preparation method according to claim 1, characterized in that: In step S3, the water wetting angle of the hydrophobic and aerophilic coating is less than 20°, and the total area of the hydrophobic and aerophilic regions accounts for 10-60% of the area of the electrode surface.
5. The preparation method according to claim 1 or 4, characterized in that: In step S3, the hydrophobic and air-philic coating is composed of a polydimethylsiloxane layer and hydrophobic nano-SiO2 bonded to the polydimethylsiloxane layer.
6. The preparation method according to claim 1, characterized in that: Step S1 specifically includes: washing the conductive carbon cloth with water and anhydrous ethanol and drying it, heating it to 450-550° C. at a rate of 10-15° C. / min and maintaining it for 2-5 h, and then washing it with water and ethanol.
7. The preparation method according to claim 1, characterized in that: Step S2 specifically comprises: preparing a mixture containing dimethylimidazole and Co 2+ The pretreated carbon cloth is suspended in the solution at an inclination angle of no more than 45° relative to the vertical direction, and is aged at 30-35°C for 2-5 h; the dimethylimidazole and Co 2+ The molar ratio of dimethylimidazole and Co is 1-12:1; 2+ In the solution, Co 2+ The concentration is 0.03~0.4 mol / L.
8. The preparation method according to claim 5, characterized in that: In step S3, the process of applying the hydrophobic and air-philic coating specifically includes: immersing the geometric gradient electrode covered with a mask in a solution containing a polydimethylsiloxane prepolymer and a curing agent for 10 to 100 seconds, taking it out and placing it in the air for 10 to 40 seconds to form a prepolymer layer; and then depositing hydrophobic nano-SiO2 on the prepolymer layer and curing it.
9. Application of a dual-gradient self-supporting hydrogen evolution electrode in electrocatalytic hydrogen evolution, characterized in that: The dual-gradient self-supporting hydrogen evolution electrode is prepared by the preparation method according to any one of claims 1 to 8.
10. The use according to claim 9, characterized in that: During the electrocatalytic hydrogen evolution process, the dual-gradient self-supporting hydrogen evolution electrode is partially immersed in the electrolyte; the hydrophobic and aerophilic regions are triangular, and the bottom edge of each hydrophobic and aerophilic region at the electrolyte surface is located above the electrolyte surface, and the top angle is located below the electrolyte surface.
Citation Information
Cited By
Ru-based oxygen evolution catalyst and preparation method and application thereof
CN120519883A
